2023
DOI: 10.4269/ajtmh.22-0504
|View full text |Cite
|
Sign up to set email alerts
|

A Countrywide Seroepidemiological Survey of Rift Valley Fever in Livestock, Uganda, 2017

Luke Nyakarahuka,
Jackson Kyondo,
Carson Telford
et al.

Abstract: In 2016, an outbreak of Rift Valley fever was reported in the Kabale District in Uganda for the first time in 48 years. Three human cases were confirmed by polymerase chain reaction, and subsequent serological investigations revealed an overall IgG seropositivity of 13% in humans and 13% in animals. In response to this reemergence, we designed a countrywide survey to determine the seropositivity of anti-Rift Valley fever virus (RVFV) IgG antibodies in livestock. Samples were collected from 27 districts and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Regarding brucellosis, goats had the highest prevalence than cattle. These findings align with previous research conducted in Uganda and Keny (Birungi et al, 2021;Kabami, 2023;Ndumu et al, 2021;Nyakarahuka et al, 2018aNyakarahuka et al, , 2023aNyakarahuka et al, , 2023bNyakarahuka et al, , 2023cNyamota et al, 2023;Tumusiime et al, 2023b).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding brucellosis, goats had the highest prevalence than cattle. These findings align with previous research conducted in Uganda and Keny (Birungi et al, 2021;Kabami, 2023;Ndumu et al, 2021;Nyakarahuka et al, 2018aNyakarahuka et al, , 2023aNyakarahuka et al, , 2023bNyakarahuka et al, , 2023cNyamota et al, 2023;Tumusiime et al, 2023b).…”
Section: Discussionsupporting
confidence: 92%
“…Multiple reports/samples taken from the same farm could have skewed distribution towards cattle, or it may be that farmers were more likely to report cattle due to their value. Previous studies in Uganda (Nyakarahuka et al, 2018(Nyakarahuka et al, , 2023a(Nyakarahuka et al, , 2023c and neighbouring countries like Kenya (Hassan et al, 2020;Muturi et al, 2023) have also found surprisingly low rates of reports of abortions in sheep. However, the small number of sheep included in the study, means we could not measure the (relative) risk of infection infection in this species.…”
Section: Such Call Centres Are Particularly Valuable For Animal Disea...mentioning
confidence: 87%
See 1 more Smart Citation